Rancang Bangun Sistem Parkir Dengan Fingerprint Menggunakan Raspberry PI - Chandra, Edwin; Putri Pratiwi, Mariska (Jurnal Ilmiah Binary STMIK Bina Nusantara Jaya Lubuklinggau, 2026)
This research presents the design and implementation of a Smart Parking System that integrates biometric authentication, license plate recognition, and dynamic tariff computation to enhance security and operational efficiency in urban parking environments. The system is developed using modular Python architecture and deployed on a Raspberry Pi platform, incorporating hardware components such as fingerprint sensors, cameras, infrared detectors, and servo motors. A graphical user interface (GUI), built with Tkinter, provides real-time updates on hardware status, captured images, and fee calculations based on a tiered pricing model (Rp 4000 base fee plus Rp 2000 per hour, capped at Rp 30,000). Dual authentication at entry and exit points ensures secure access control, while automated gate operation and ultrasonic clearance detection streamline traffic flow. The system supports structured CSV logging with weekly data rollovers to facilitate traceability and long-term monitoring. Experimental results demonstrate the system’s reliability, scalability, and maintainability, indicating its potential for deployment in smart city infrastructure and automated parking management.